STUDI EVALUASI TERHADAP AMANDEMEN UUD 1945 (AMANDEMEN SEBAGAI UPAYA PEMENUHAN KEBUTUHAN HUKUM MASYARAKAT INDONESIA) - Wijayanti, Septi Nur (Jurnal Media Hukum, 2009)
The four amendments of Indonesian Constitution 1945 taking place in 1999, 2000, 2001 and 2002 still have weaknesses, especially in terms of substance when inconsistencies exist. For example 1) the presidential system applied which violates the system such as the president’s accountability to the People’s Consultative Assembly (not clearly stated), the intervention of the House of Representative to president’s policy implementation, impeachment given by People’s Consultative Assembly, and the unclear responsibilities and accountability of the vice president; 2) the unbalanced bargaining power of the Regional Representative Council (DPD) in form of bicameral representative in the House of Representative; and 3) the controversial existence of the Judicial Commission. Therefore, an evaluation needs to be carried out to create a better constitution in the state administration. Running a nation should have a clear concept of a nation so that the politicians have strong principles to take action and create policies. On the other hand, the legal need of the society has to be fulfilled.